Oligoclonal banding in MS. - Ebers, G (1984)
Multiple sclerosis is considered to be a putative immunopathologic disease and there has been considerable effort over the years to prove an autoimmune etiology for it. To dat, the evidence is all indirect and there is no proof of either antibody and/or cell-mediated hypersensiivity to any single identifiable CNS constituent whether a constituent of normal CNS or specific to the CNS of MS patients.